A new dibenzothiophene-based dual-channel chemosensor for cyanide with aggregation induced emission. Issue 43 (21st October 2019) - Zou, Qiqi; Tao, Furong; Xu, Zhen; Ding, Yunqiao; Tian, Yan; Cui, Yuezhi
Abstract : A new dibenzothiophene-based barbituric acid derivative (DTB ) with an aggregation induced emission (AIE) effect was synthesized as a naked-eye colorimetric and fluorescent probe for CN − . Abstract : A new dibenzothiophene-based barbituric acid derivative (DTB ) with an aggregation induced emission (AIE) effect was synthesized as a naked-eye colorimetric and fluorescent probe for CN − . The UV-vis spectra and fluorescence spectra of DTB in a DMSO/H2 O mixture changed with different water fractions ( f w ). Nano-aggregates of DTB were formed with the strongest fluorescence emission when f w reached 99%. Furthermore, DTB expressed good selectivity and high sensitivity for CN − in 99% aqueous DMSO solution. The sensing mechanism of DTB for CN − was confirmed by 1 H NMR titration, HRMS spectra, Job's plot and DFT calculations. Furthermore, DTB detected CN − with a low detection limit (21.6 nM), wide pH range (4–10), high anti-interference ability and fast response time (10 s). Moreover, DTB -based test strips were prepared for CN − detection, and DTB could detect CN − in real water samples.